Latin American Research on Bariatric Surgery: a Bibliometric Study - Toro Huamanchumo, Carlos J. (2020)
We performed a bibliometric analysis of Latin American documents published between 1984 to 2019 in Scopus-indexed journals. A total of 1856 documents were analyzed. The annual scientific production was 64 documents per year, with an annual increase rate of 15.9%. The countries with the highest scientific production on BS were Brazil (64.7%) and Chile (14.5%). Most of the publications were original (76.6%) and review articles (11.9%). The journal with the highest publication record was “Obesity Surgery” (25.8%). The extra-regional collaboration was mainly with the USA. In conclusion, Latin American scientific production on BS has shown a significant increase in recent years. However, more participation is needed, fostering intra-regional collaboration and involving universities and health institutions in BS research.